Loss aversion and US European security policy, 1989 to 1999 - Landrum, Jerry (Kansas State University, 2018)
From 1989 to 1999, the US had an opportunity to end its rivalry with Russia. However, a “loss aversion heuristic” dominated the decision-making processes of George Bush and Bill Clinton resulting in policies that provoked Russian fears of encirclement. This “loss aversion heuristic” manifested in four key security decisions: the reunification of Germany within NATO, NATO expansion to newly independent states, the Balkans interventions, and the nuclear non-proliferation regime. Although initially suspicious of Gorbachev, Bush eventually pursued a policy of supporting his reforms. However, as the administration came to terms with the inevitability of German reunification and increased European integration as outlined in the Single European Act of 1987, worries about the US leadership role in Europe emerged. By the fall of 1989, Bush backed German reunification to bolster pro-NATO political parties in Germany. As he assumed the presidency in 1993, Clinton wanted to increase financial assistance to Russia. However, when it came to security issues, Clinton’s fear of losing democratic gains in Eastern Europe to an emerging Russian nationalist movement made him less conciliatory to Russia. Despite Yeltsin’s dismay, Clinton pushed for NATO’s enlargement to protect the newly independent states. The same “loss aversion heuristic” was in play with the NATO interventions in the Balkans in 1995 and 1998. Criticisms of NATO’s ineffectiveness at preventing genocide on the continent called into question the necessity of a European security organization that could not provide security. Even though the interventions cemented a continued rivalry with Russia, the US backed them as a means of protecting the relevance of NATO. These decisions had implications to the US policy of protecting the nuclear non-proliferation regime. Instead of securing a nuclear security partner, US policy contributed to Russians selling technology to rogue regimes, and they resisted US attempts to create an Anti-Ballistic Missile Defense (ABM) system in Eastern Europe. In this way, US policy success in securing NATO resulted in decreased nuclear security. In the first three security decisions, the US overestimated the probability of loss making them unable to consider a more cooperative posture vis-à-vis Russian security concerns. The result of this loss aversion was the protection of NATO and the loss of cooperation on the nuclear non-proliferation regime.
Keywords: Prospect theory; Cold War; German reunification; NATO enlargement; Bosnian War; Kosovo War